Bidirectional Dielectric Barrier Discharge (DBD) Plasma Generator for Radar Cross Section (RCS) Reduction of Dihedral Corner Reflector in X-Band - Changseok Cho; Jinwoo Jung; Yongshik Lee; Minsu Choi; Shinjae You; Hyunsoo Lee; Jungje Ha; Cheonyeong Kim (IEEE Access)
This study proposes a bidirectional dielectric barrier discharge (DBD) plasma generator, based on coplanar electrodes, for radar cross-section (RCS) reduction of a dihedral corner reflector. The bidirectional discharging mode, achieved through a simple modification of the bias circuit, increases the plasma layer thickness from less than 1 mm in the unidirectional mode—confined between the coplanar electrodes—to 4.572 mm in this work, corresponding to the distance between the coplanar electrodes and the bottom plate, which serves as an additional electrode in the bidirectional mode. The increased plasma thickness significantly enhances the interaction between the plasma and incident electromagnetic waves, overcoming the limited RCS reduction performance typically observed with coplanar electrode DBD plasmas, while retaining their simplicity and versatility. Moreover, while previous plasma-based RCS reduction approaches have primarily focused on planar targets, this study applies the method to a three-dimensional dihedral corner reflector with a 90° angle, modeling structures that often dominate the RCS of real-world targets. Experimental results for normal incidence and linear polarization, measured under far-field conditions in the X-band, reveal that the bidirectional discharging mode achieves an additional RCS reduction of up to 9.0 dB compared to the unidirectional mode, resulting in a maximum RCS reduction of 20.9 dB at 9.8 GHz. Additionally, a $46.3%~10$ -dB RCS reduction bandwidth was achieved, maintaining an RCS reduction above 10 dB across the entire X-band and exceeding 15 dB over the majority of the band. Within the X-band, an average RCS reduction of 16.3 dB was observed. These results demonstrate that the proposed plasma-based technology can not only effectively reduce the RCS of practical geometries but also deliver bandwidth performance that surpasses conventional counterparts.